Diversity of Collembola on Various Post-Rehabilitation Land Covers - Astanovia Dewi, Risandika; Triyogo, Ananto; Faridah, Eny (Jurnal Manajemen Hutan Tropika, 2024)
The success of rehabilitation has altered environmental conditions from critical land to new habitats for living organisms. One of the representative and sensitive mesofauna to environmental changes is Collembola. Various vegetation cover almost all of the rehabilitation area, which has impacts on microclimate and soil quality as important factors to Collembola existence. This study investigated the diversity and abundance of Collembola and its relation to environmental factors on various land covers, including teak, grass, and mixed stand land cover. Data were collected in an observation plot of 20 m × 20 m using purposive samples, including environmental measurements, Collembola collection, and soil samples for physical and chemical analysis. The results showed that different land covers affected the abundance and diversity of Collembola, even though the statistical analyses of TLC, GLC, and MLC were not significantly different. However, TLC has a higher litter thickness and organic material than the other land cover types. A few families of Collembola, such as Cyphoderidae, Brachystomellidae, Katiannidae, Isotomidae, Oncopoduridae, and Isotogastruridae, show their correlation to climatic and edaphic factors in a certain land cover.